2008
DOI: 10.1097/bsd.0b013e3181583b56
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Unstable Lower Cervical Spine Injuries by Anterior Instrumented Fusion Alone

Abstract: Anterior instrumented fusion is at least as efficient as the posterior procedure in the management of cervical spine injuries and it also has several advantages. Most of such injuries, including the dislocations, can be managed with anterior instrumented fusion alone. Simple means of immobilization such as the hard collar suffice, and secondary posterior fixation is rarely, if ever, necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 62 publications
1
20
0
7
Order By: Relevance
“…[3][4][5][6] Usually the patients treated at the Risoleta Tolentino Neves University Hospital with suspected cervical fracture dislocation, confirmed by clinical and radiographic evaluation, are not routinely subjected to the installation of a cranial halo. Cranial traction, even with light load, has been demonstrated to lead to deficits in the majority of patients with certain injuries, as evidenced by the study of Grant et al 7 The results of this study are consistent with the literature, similar to those reported by Wiseman et al 6 and Lambiris et al 10 Good clinical/functional results were achieved in 28 patients (82.35% of good results with open reduction and only an anterior approach) and in six patients (reduction was not achieved in 17.65%, necessitating anterior and posterior approaches). No iatrogenic lesions were identified (0% of neurological damage) that could have occurred with the use of cervical traction.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[3][4][5][6] Usually the patients treated at the Risoleta Tolentino Neves University Hospital with suspected cervical fracture dislocation, confirmed by clinical and radiographic evaluation, are not routinely subjected to the installation of a cranial halo. Cranial traction, even with light load, has been demonstrated to lead to deficits in the majority of patients with certain injuries, as evidenced by the study of Grant et al 7 The results of this study are consistent with the literature, similar to those reported by Wiseman et al 6 and Lambiris et al 10 Good clinical/functional results were achieved in 28 patients (82.35% of good results with open reduction and only an anterior approach) and in six patients (reduction was not achieved in 17.65%, necessitating anterior and posterior approaches). No iatrogenic lesions were identified (0% of neurological damage) that could have occurred with the use of cervical traction.…”
Section: Discussionsupporting
confidence: 83%
“…In fractures type B and C of the AO-ASIF in which uni-or bifacet dislocation occurs, it is possible to achieve reduction through a anterior surgical approach with discectomy and distraction of the vertebral bodies through the Caspar distractor or laminar distractor. 6,10 Taking into consideration that it takes a high-energy trauma that usually causes serious consequences to the patient in these cases, cases in which there are severe unilateral or bilateral dislocations of facets, or that appear in the form of intervertebral distraction, require careful analysis of the examiner in both the clinical and radiological evaluation, and in the indication for surgical treatment. The cervical traction in these cases is potentially dangerous as it can cause neurological damage, because all of the ligaments are ruptured and show deficits, concentrating the force on the already bruised muscles and cervical neural elements that are barely resistant to strain; besides, it presents risks related to neurological worsening due to the migration of the intervertebral disc into the spinal canal.…”
Section: Discussionmentioning
confidence: 99%
“…Não havendo lesão ligamentar, a via posterior não foi empregada. A maioria desses pacientes foi submetida à corpectomia do nível correspondente, associada ou não à artrodese, com o intuito de dar suporte anterior à coluna cervical fraturada 14 . Já nas lesões do Tipo B, a quase totalidade desses pacientes foi operada (85%) e, quando isso ocorreu, diferentemente do Tipo A, realizou-se predominantemente a cirurgia por via posterior, considerando-se a lesão ligamentar posterior presente.…”
Section: Discussionunclassified
“…Deve-se considerar também a maior frequência do mecanismo em flexão em relação ao de extensão. Os pacientes operados por via anterior tinham lesão ligamentar anterior ou insuficiência de sustentação por fratura associada do corpo vertebral 14 . Com as lesões do Tipo C, de modo semelhante ao Tipo B, quase todos os casos foram submetidos à cirurgia (81%), a qual foi realizada quase exclusivamente por via posterior (95%).…”
Section: Discussionunclassified
See 1 more Smart Citation